Hypertriglyceridemia may contribute to stroke and pancreatitis: A case report and review of the literature - Zhang, Mingyu; Yin, Taoyuan; Xia, Feng; Xia, Suhong; Zhou, Wangdong; Zhang, Yu; Han, Xu; Zhao, Kai; Feng, Lina; Dong, Ruonan; Tian, Dean; Yu, Yan; et al. (Frontiers in Endocrinology, 2022)
Hypertriglyceridemia is one of the most common clinical dyslipidemia. Nevertheless, stroke and acute pancreatitis co-occurrence due to hypertriglyceridemia are extremely rare. We present a case of hypertriglyceridemia-associated stroke and pancreatitis in a 39-year-old woman. The patient's laboratory tests reported high triglyceride concentrations beyond the instrument's detection range, and radiological examination showed typical signs of cerebral infarction and acute pancreatitis. The patient received combined blood purification therapy, intravenous thrombolysis with urokinase, and conservative treatment of pancreatitis. We discuss the clinical features, pathogenesis, diagnosis, and treatment of hypertriglyceridemic stroke and pancreatitis combined with the relevant literature. We reviewed the mechanisms by which triglycerides contribute to atherosclerosis and acute pancreatitis, mentioning the role played by mitochondria. We point out the superiority of combined blood purification therapy and caution physicians about the effects of prescribed drugs on blood lipids.